A Randomized Comparative Trial on the Therapeutic Efficacy of Topical Aloe vera and Calendula officinalis on Diaper Dermatitis in Children - Yunes Panahi; Mohamad Reza Sharif; Alireza Sharif; Fatemeh Beiraghdar; Zahra Zahiri; Golnoush Amirchoopani; Eisa Tahmasbpour Marzony; Amirhossein Sahebkar (The Scientific World Journal)
Introduction. Diaper dermatitis (DD) is a common inflammatory disorder among children and infants. The objective of the present randomized and double-blind trial was to compare the therapeutic efficacies of Aloe vera cream and Calendula officinalis ointment on the frequency and severity of DD in children. Methods. Sixty-six infants with DD (aged < 3 years) were randomized to receive either Aloe cream (n=32) or Calendula ointment (n=34). Infants were treated with these drugs 3 times a day for 10 days. The severity of dermatitis was graded at baseline as well as at the end of trial using a 5-point scale. The adverse effects of study medications were assessed during the trial. Results. Although improvement in the severity of DD was observed in both treatment groups (P<0.001), patients receiving Calendula ointment had significantly fewer rash sites compared to Aloe group (P=0.001). No adverse effect was reported from either of the medications. Discussion. The evidence from this study suggests that topical Aloe and in particular Calendula could serve as safe and effective treatment for the treatment of diaper dermatitis in infants.